2010
DOI: 10.1152/ajpcell.00096.2010
|View full text |Cite
|
Sign up to set email alerts
|

Transition of kidney tubule cells to a senescent phenotype in early experimental diabetes

Abstract: Diabetic nephropathy is the commonest cause of end-stage renal disease. Inordinate kidney growth and glomerular hyperfiltration at the very early stages of diabetes are putative antecedents to this disease. The kidney is the only organ that grows larger with the onset of diabetes mellitus, yet there remains confusion about the mechanism and significance of this growth. Here we show that kidney proximal tubule cells in culture transition to senescence in response to oxidative stress. We further determine the te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
59
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 63 publications
9
59
0
Order By: Relevance
“…Expression of p27 increases in response to hyperglycemia or diabetes, which, on the basis of studies in nontubular cells, can be attributed to induction by PKC (170) and TGF␤ (69). Diabetes also increases the renal expression of the CDK p21 (6,127). Consistent with a potential role of p21 in the switch from hyperplasia to hypertrophy in the diabetic kidney, loss of p21 increases tubular cell proliferation (6) (Fig.…”
Section: Unique Growth Phenotype Of the Diabetic Proximal Tubulesupporting
confidence: 59%
See 1 more Smart Citation
“…Expression of p27 increases in response to hyperglycemia or diabetes, which, on the basis of studies in nontubular cells, can be attributed to induction by PKC (170) and TGF␤ (69). Diabetes also increases the renal expression of the CDK p21 (6,127). Consistent with a potential role of p21 in the switch from hyperplasia to hypertrophy in the diabetic kidney, loss of p21 increases tubular cell proliferation (6) (Fig.…”
Section: Unique Growth Phenotype Of the Diabetic Proximal Tubulesupporting
confidence: 59%
“…Transient induction of p21, p16 INK4A (p16), and/or p27 are involved in the prototypical senescent arrest or senescent-like growth arrest (8,178). Recent studies by Satriano et al (127) revealed that STZ-diabetic kidneys exhibited an early transient induction of growth-phase components followed by their suppression at day 10 after the onset of diabetes. This was concurrent with the induction of CDK inhibitors p16, p21, and p27 and markers of senescence, including expression of senescence associated beta-galactosidase activity in cortical tubules (127).…”
Section: Unique Growth Phenotype Of the Diabetic Proximal Tubulementioning
confidence: 99%
“…A unique feature of diabetesrelated hypertrophy is that the signaling pathways are initially mediated by signaling pathways resulting in increased cell proliferation (17). Shortly after proliferation, however, the environment switches to promote cellular senescence and hypertrophy (17,33). It has been suggested that functional hypertrophy (increased GFR) contributes to the development of diabetic nephropathy (23).…”
Section: Discussionmentioning
confidence: 99%
“…This phosphorylation of Cx43, like that induced by high glucose in vascular smooth muscle cells, would interfere with gap junction expression, distribution, degradation and function [15,17,37]. Indeed, Satriano et al [38] have reported reduced levels of Cx43 in kidney from a streptozotosin-induced rat model of type 1 diabetes. Sawai et al [39] noted that Cx43 abundance was distributed non-uniformly in human glomerular podocytes of type2 diabetes patients and that these abnormalities in Cx predict poor renal prognosis.…”
Section: Discussionmentioning
confidence: 99%